THE EFFECTS OF TECHNOLOGY ON PEER RELATIONSHIPS AND INTERPERSONAL UNDERSTANDING: A CASE STUDY AT A TEACHER EDUCATION INSTITUTE IN MALAYSIA. - Sathappan, Ramesh; Sathappan, Malini (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
In this information age, technology such as the internet has a profound effect on the peer relationships and interpersonal understanding.The study incorporates the views of authors on the subject. There are advantages and disadvantages in using electronic communication for interpersonal understanding. It promotes better understanding, cooperation and closer peer relationship among students and teens. However, it also has a darker side. It can lead to cyberbullying. Information and communication technology has transformed the classroom scenario by the use of videos, etc. in the teaching and learning process. Students have become more sophisticated in applying electronic devices for their academic performance. The findings show that majority of the students prefer to use e-mail in their interaction. It is recommended that teachers and parents monitor the students to ensure there is no abuse and misuse of technology.